(untitled) (Global Journal of Human-Social Science, 2023)
The article is devoted to the analysis of features of the programs of murals of modern Ukrainian Orthodox churches mainly in the East of Ukraine from the point of view of cultural studies Changes in the programs of church murals changes in the styles and techniques of murals are taken into account Among the modern trends in the murals of Orthodox churches painted in the 21st century the following can be distinguished a special severity of the dedication of the temple in the program of its painting the possibility of a creative approach by customers and icon painters in compiling one or another program for painting the temple the preference of the Byzantine style to other styles the revival of interest in fresco It should be noted the results of the influence of the visual turn on the monumental church painting